Early hydration and compressive strength of steam cured high-strength concrete based on simplex centroid design method. (December 2022) - Wang, Panqi; Li, Xiaoguang; Huo, Xiaoliang; Ali, Saddam; Sun, Jiazhen; Qin, Jinyi; Liang, Kun; Liu, Yunxiao
Abstract: To obtain the precast concrete elements with high strength at an early stage, and strike a balance among mechanical properties, economic benefits and sustainable development. The heat of hydration, bound water content, calcium hydroxide content (CH), compressive strength and porosity of high-strength concrete (HSC) with cement–silica fume–fly ash micro-bead binder at 85 °C were investigated. The ternary binder formulations were the designed using simplex centroid design method. The results show that the appropriate amount of silica fume and fly ash micro-bead increases the total heat release and compressive strength of HSC, and reduce the CH content and porosity. Silica fume incorporation advances the induction period end time, while fly ash micro-bead increases the induction period end time. The pozzolanic reactivity of silica fume was greater than that of fly ash micro-bead. The effect of silica fume on 28 days strength was particularly obvious, and fly ash micro-bead have more significant improvement in early strength. The porosity shows a strong correlation with the compressive strength. The findings of this study are a worth reference for precast concrete manufacturers and can help to guide future studies.